2011
DOI: 10.1177/0194599811419457
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Hyaluronic Acid in Human Vocal Folds in Young and Old Subjects

Abstract: HA concentrations are higher in the cover and ligament compared with the muscle in both genders and age groups, and there is a higher HA concentration in ligament compared with the muscle of young subjects of both genders. HA levels in the cover samples of younger women showed great variability that may relate to ovarian hormone levels, reflecting different phases of the menstrual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…Other than striated muscles, elastic fiber-mediated connections have been described in the larynx [30,31], the middle ear [32] and the urethra [9] (Figure 1…”
Section: Levator Ani Muscle Collagenous Fibers and Elastic Fibersmentioning
confidence: 99%
“…Other than striated muscles, elastic fiber-mediated connections have been described in the larynx [30,31], the middle ear [32] and the urethra [9] (Figure 1…”
Section: Levator Ani Muscle Collagenous Fibers and Elastic Fibersmentioning
confidence: 99%
“…Lebl et al, 14 using a more reliable histochemical technique, revealed a clear distinction between layers with more pronounced HA staining in the intermediate and deep lamina propria in comparison with the superficial layer. Finally, Korn et al 20 found a higher HA concentration in the cover (superficial lamina propria) among women compared with men.…”
Section: Discussionmentioning
confidence: 95%
“…Elastic fiber-rich connective tissues have been well described in the larynx [16] [17], the middle ear [18] and the urethra [19]. According to Hinata et al [19], the male urethra contains a much greater amount of elastic fibers than the female urethra.…”
Section: Discussionmentioning
confidence: 99%